Examining the influence personality factors on knowledge sharing intention among employees of two selected banks (2013)
This study examined the influence of personality factors (that is, need for achievement, need for affiliation, and need for power) on knowledge sharing intention. A cross-sectional survey design was adopted while a total of 207 employees selected from two commercial banks in Nigeria using accidental sampling technique participated in the study. The participants were made of 113 (54.6%) males and 94 (45.4%) females. Their ages ranged between 26 and 47 years with a mean of33.35 and standard deviation of 3.87. A structured questionnaire with three sections was used for data collection. Three hypotheses were tested using t-test of independent mean. The results showed that need for achievement [t (205) = 2.07, P < 0.05] and need for power [t (205) = 16.79, P< .001] significantly influenced knowledge sharing intention, while need for affiliation did not [t (205) = 1.05, P > 0.05]. These findings suggested the need for human resource personnel of various banks in Nigeria to design recruitment and selection strategies that can help them identify employees with high need for achievement and need for power; since they are more motivated to share their knowledge.